PEMBERDAYAAN KELOMPOK WANITA TANI (KWT) ASRI DI DUKUH DAWUNG KELURAHAN KEDUNGPANE KECAMATAN MIJEN KOTA SEMARANG - Afifah, Siti Nur; Ilyas, Ilyas (Journal of Nonformal Education and Community Empowerment, 2021)
The purpose of this study is to describe the process of empowerment Asri Farmer Women Group (KWT) in Dukuh Dawung and the impact of the empowermentprocess of Asri Farmer Women Group (KWT) in Dukuh Dawung. This studyused a descriptive qualitative approach. The data were taken by observation,interviews, and documentation. The validity technique used source triangulation.Data analysis techniques in this research were using data collection, datareduction, data presentation, and drawing conclusions. The results of the studyfound that the empowerment of Asri KWT in Dukuh Dawung included (1)identification that consist of potentials of dukuh, problems of dukuh and group,and group opportunities, (2) planning, consist of awareness, recruitment ofmembers and assistants, field preparation. (3) implementation, consist of types ofactivities, medias, materials, participations, and motivations, and (4) programmonitoring and evaluation on the process and results of the activities. The impactobtained by the empowerment of KWT Asri is that it can improve independence,skills, and harmony among KWT Asri members.